Type designations for sap beetles in the subfamily Carpophilinae Erichson (Coleoptera: Nitidulidae) housed in the Natural History Museum, London - Powell, Gareth S.; Martin, Gavin J. (Zootaxa, 2019)
The subfamily Carpophilinae, in particular the genus Carpophilus Stephens, represents one of the most speciose lineages within Nitidulidae. The subfamily was first recognized by Erichson (1843) in a much broader sense, including what is now the Cillaeinae. According to Kirejtshuk (2008), there are seven genera and 13 subgenera within Carpophilinae. To date, however, no comprehensive tribal or generic phylogenetic reconstructions have been published for the subfamily. This work constitutes a preliminary stage of a larger project that will address the subfamily in a rigorous taxonomic and systematic framework. A stable taxonomic foundation for Carpophilus species and other Carpophilinae taxa is needed to ensure the validity of future work in the subfamily. Herein we designate lectotypes and paralectotypes and confirm holotypes for 14 species of carpophiline sap beetles following ICZN (1999) articles 73.1 and 74.1.